An Analysis of the Implementation of the Play-Based Learning Method to Improve Learning Concentration among Elementary School Students - Shafarina, Annisa Yola; Ridho, Muhammad Rasyid (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2025)
Learning for Grade 2 elementary school students requires innovative instructional approaches to improve students’ concentration during the learning process. Young learners tend to have limited attention spans, making traditional lecture-based methods less effective. Therefore, play-based learning is considered a relevant approach, as it integrates academic content into enjoyable and interactive activities. This study aims to analyze the implementation of the play-while-learning method and its impact on students’ learning concentration. The research employed a qualitative descriptive method using classroom observations, learning activity documentation, and evaluation of student engagement during instructional sessions. The results indicate that the play-while-learning method significantly increased students’ learning concentration, participation, and motivation. Students demonstrated higher levels of engagement, better understanding of learning materials, and improved social interaction skills compared to those taught using conventional teaching methods. Furthermore, learning activities designed through games encouraged active participation and sustained attention throughout the lesson. In conclusion, the play-while-learning method proves to be an effective instructional strategy for enhancing learning concentration among Grade 2 elementary school students. This method can serve as a practical reference for teachers in creating a more productive, engaging, and enjoyable learning environment.